EFEKTIVITAS KUALITAS LAYANAN DI TENGAH PERSAINGAN ONLINE TRAVEL AGENT MELALUI KEPUASAN PELANGGAN - Saragih, Darwin Raja Unggul; Nasruddin, Nasruddin (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2022)
This research aims to determine the effect of service quality on customer satisfaction through the purchasing decision of airlines ticket products at Holiday Indonesia. This research is descriptive quantitative research, with a population of customers who have purchased airplane tickets at Holiday Indonesia at least two times in 2020 as many as 415 customers. The sampling technique in this study used the purposive sampling technique, namely 119 samples that had met the criteria. Data processing uses path analysis as the method used to determine the direct and indirect effects between variables and the Sobel test to determine whether purchasing decisions are capable of being a mediator between the relationship between service quality and customer satisfaction. The results show that service quality has a positive and significant effect on purchasing decisions. Service quality has a positive and significant effect on customer satisfaction and purchasing decisions have a positive and significant impact on customer satisfaction. The relationship between service quality and customer satisfaction can be mediated by purchasing decisions with a Z value (mediation), and concluded that the purchasing decision variable has a significant influence as a mediator between the relationship between service quality and customer satisfaction.